2019
DOI: 10.1016/j.jvir.2018.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Venous Stenosis Angioplasty in a Murine Arteriovenous Fistula Model

Abstract: Purpose: To develop a clinically relevant model of percutaneous transluminal angioplasty (PTA) of venous stenosis in mice with arteriovenous fistula (AVF); to test the hypothesis that there is increased wall shear stress (WSS) after PTA; and to histologically characterize the vessels.Materials and Methods: Thirteen C57BL/6J male mice, 6-8 weeks old, underwent partial nephrectomy to create chronic kidney disease. Twenty-eight days later, an AVF was created from the right external jugular vein to the left caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…Thus, inflammatory cells may also contribute to the greater intimal hyperplasia formation following angioplasty. In contrast to our findings, Cai et al [24] reported a significant reduction in intimal plus medial area, along with decreased α-SMA and CD68 expressions 14 days following percutaneous transluminal angioplasty in a murine model. Moreover, there is a recent study from Cai et al [25] demonstrating sex differences in treatment response to angioplasty in a murine AVF model.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, inflammatory cells may also contribute to the greater intimal hyperplasia formation following angioplasty. In contrast to our findings, Cai et al [24] reported a significant reduction in intimal plus medial area, along with decreased α-SMA and CD68 expressions 14 days following percutaneous transluminal angioplasty in a murine model. Moreover, there is a recent study from Cai et al [25] demonstrating sex differences in treatment response to angioplasty in a murine AVF model.…”
Section: Discussioncontrasting
confidence: 99%
“…The important role of collagen density in vascular remodeling following angioplasty has been previously reported to be associated with constrictive remodeling and restenosis [30]. Consistent with a previous report from Cai et al [24], in the present study, we have observed a significant increase of collagen expression in both AVFartery and vein in the angioplasty group compared to the control at 35 days post-AVF creation (Fig. 7).…”
Section: Discussionsupporting
confidence: 92%
“…Percutaneous transluminal angioplasty (PTA) is the first line treatment for malfunctioning AVF caused by vascular stenosis 2 . After PTA, AVF restenosis develops due to restenosis caused by venous neointimal hyperplasia (VNH) resulting in poor patency 3 , 4 . As a consequence, therapeutic measures are needed to improve AVF patency following PTA.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the normal endothelium expresses Ier3 10 , but the expression in stenotic endothelial cells from human AVFs is unknown. The gene and protein expression of IER3 was determined in outflow veins removed from mouse model of PTA 4 . We decreased Ier3 gene expression using 1,25 NP and the changes in VNH/VS were determined using histomorphometric analysis, immunohistologic changes, with hemodynamic changes assessed with Doppler ultrasound, and gene expression 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation